Stock de carbono en especies arbóreas del espinal entrerriano - Sione, Silvana María José; Ledesma, Silvia Gabriela; Rosenberger, Leandro Javier; Oszust, José Daniel; Maciel, Gabriel Omar; Wilson, Marcelo German; Andrade-Castañeda, Hernán J.; Sasal, Maria Carolina (Universidad Nacional de Entre Ríos, 2023)
Proyecto PID 2182 (UNER)